Differences in the influence of the board of directors and the board of commissioners on real earnings management: empirical evidence from Indonesia - Mardianto; Karina, Ria; Edi, Edi (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
Purpose – This research investigates the influence of the Board of Directors (BOD) and the Board of Commissioners (BOC) on real earnings management (REM) practices in Indonesian manufacturing companies. Real earnings management involves genuine alterations to operational decisions that affect financial reporting.Design/methodology/approach – The research uses a sample of manufacturing firm listed on Indonesia Stock Exchange (BEI) from 2016 to 2022 and uses panel data regression techniques, including the Pooled Least Square (PLS) and Fixed Effect Model (FEM), to examine the effects of BOD and BOC characteristics on REM. The empirical analysis considers multiple proxies for BOD and BOC attributes, such as board size, independence, meeting frequency, and expertise. Additionally, control variables including leverage, firm size, and growth indicators are incorporated into the analysis.Findings – The findings reveal a significant positive relationship between the presence of BOD and REM activities. In contrast, the presence of BOC demonstrates a non-significant but negatively associated impact on REM. Furthermore, the research identifies the moderating role of BOC in strengthening the relationship between BOD and REM.Research limitations/implications – The research contributes to the existing literature by providing empirical insights into the roles of BOD and BOC in shaping REM practices within the Indonesian manufacturing context. These findings highlight the importance of board characteristics in influencing financial reporting decisions and emphasize the need for effective corporate governance mechanisms to mitigate opportunistic behaviors related to earnings management.Practical implications – Enhancing corporate governance practices, provide an input for more effective board composition, increase the investor confidence and transparency, enhance policy implications and provide advice for company’s long-term performance focus.Originality/value – This research addresses a gap in the literature by focusing on the Indonesian context. Use the BOC to moderate the relationship between BOD and REM may be less common in the context of Indonesia and even in regional focus.